The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1093/ajcn/nqz163
|View full text |Cite
|
Sign up to set email alerts
|

The effect of eggs on early child growth in rural Malawi: the Mazira Project randomized controlled trial

Abstract: Background Stunted growth is a significant public health problem in many low-income countries. Objective The aim of this study was to evaluate the impact of 1 egg per day on child growth in rural Malawi. Design We conducted an individually randomized controlled trial in which 660 children aged 6–9 mo were equally allocated into an intervention (1 egg/d) or co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
128
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(139 citation statements)
references
References 20 publications
(24 reference statements)
9
128
1
1
Order By: Relevance
“…Among effect modifiers, we found a consistent pattern that subgroups of children who were less vulnerable at baseline tended to show positive effects of the intervention, for example, those with higher initial LAZ, mild to no food insecurity, higher household wealth, and higher maternal education. A similar pattern was found for the main outcome of the trial, that is a positive effect of the intervention on LAZ among children of mothers with higher maternal formal education ( 5 ). Thus, although the primary analyses did not reveal robust effects of the intervention, it is possible that the intervention is effective for this population under some conditions.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Among effect modifiers, we found a consistent pattern that subgroups of children who were less vulnerable at baseline tended to show positive effects of the intervention, for example, those with higher initial LAZ, mild to no food insecurity, higher household wealth, and higher maternal education. A similar pattern was found for the main outcome of the trial, that is a positive effect of the intervention on LAZ among children of mothers with higher maternal formal education ( 5 ). Thus, although the primary analyses did not reveal robust effects of the intervention, it is possible that the intervention is effective for this population under some conditions.…”
Section: Discussionsupporting
confidence: 76%
“…One potential explanation for the lack of overall effects of the intervention on child development was that adherence to egg consumption may have been low, especially among more vulnerable children. However, multipass 24-h dietary recalls administered at the baseline, 3-mo, and 6-mo visits suggested that adherence was relatively high ( 5 ). According to these recalls, at baseline, only 4% of children consumed eggs on the previous day.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Association between LAZ or stunting in children(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) months of age) and contemporaneous ASF consumptionThe table reports estimation results using FE panel regressions. The outcome variable in Panel A is child's LAZ and a dummy variable equal to 1 if the child is stunted in Panel B.Co-variates and control variables: child consumed starchy staples, dark green leafy vegetables, vitamin A rich fruits and vegetables, other fruits and vegetables, legumes, nuts and seeds, child's age, age squared, age cube, a dummy variable equal to 1 if the child is a girl, a dummy variable equal 1 if the child had diarrhea in the past two weeks, the caregiver's years of education, the mothers height, a dummy equal to 1 if the household has an improved latrine.…”
mentioning
confidence: 99%